Palliative Measures with Ethanol Gallbladder Ablation and Endobiliary Radiofrequency Ablation Followed by Endoscopic Biliary Stent Placement in an Advanced Case of Common Bile Duct Cancer: A Case Report - Lee, Yong-woo; Kim, Hyun Jeong; Lee, Sang Yub; Heo, Jun; Jung, Min Kyu (The Korean journal of gastroenterology, 2020)
Endobiliary radiofrequency ablation (RFA) is a procedure performed widely to induce locoregional tumor control by the transfer of thermal energy to the lesion and subsequent tumor necrosis. A 72-year-old male with a prior history of acute calculous cholangitis and perforated cholecystitis was admitted to the Kyungpook National University Hospital complaining of fever and nausea. He had an indwelling percutaneous transhepatic gallbladder drainage (PTGBD) catheter from the previous episode of perforated cholecystitis. An abdominal CT scan showed marked dilation of both the intrahepatic and extrahepatic bile ducts. Common bile duct cancer was confirmed histologically after an endobiliary biopsy. A surgical resection was considered to be the initial treatment option. During open surgery, multiple metastatic nodules were present in the small bowel mesentery and anterior abdominal wall. Resection of the tumor was not feasible, so endobiliary RFA was performed prior to biliary stenting. Cholecystectomy was required for the removal of the PTGBD catheter, but the surgical procedure could not be performed due to a cystic ductal invasion of the tumor. Instead, chemical ablation of the gallbladder (GB) with pure ethanol was performed to breakdown the GB mucosa. Palliative treatment for a biliary obstruction was achieved successfully using these procedures. In addition, a PTGBD catheter was removed successfully without significant side effects. As a result, an improvement in the patient's quality of life was accomplished.